Solve: (3"X" - 2)/3 + (2"X" + 3)/2 = "X" + 7/6 - Mathematics

Advertisements
Advertisements
Sum

Solve: `(3"x" - 2)/3 + (2"x" + 3)/2 = "x" + 7/6`

Advertisements

Solution

`(3"x" - 2)/3 + (2"x" + 3)/2 = "x" + 7/6`


`=> (2(3"x" - 2) + 3("2x" + 3))/6 = "x" + 7/6`


`=> ("6x" - 4 + "6x" + 9)/6 = ("6x" + 7)/6`


`=> ("12x" + 5)/6 = ("6x" + 7)/6`

⇒ 6(12x + 5) = 6(6x + 7)

⇒ 72x + 30 = 36x - 42

⇒ 72x - 36x = 42 - 30

⇒ 36x = 12

x = `12/36`

∴ x = `1/3`

Concept: Solving Linear Inequations
  Is there an error in this question or solution?
Chapter 14: Linear Equations in one Variable - Exercise 14 (C) [Page 169]

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (C) | Q 1.11 | Page 169
Share
Notifications



      Forgot password?
Use app×